2007
DOI: 10.1080/17518420701309758
|View full text |Cite
|
Sign up to set email alerts
|

The psychological sequelae on mothers of thermally injured children and adolescents: Future directions: Part 3

Abstract: Part 3 of this study focused on maternal psychopathology and relationship with their children in three groups, assessed in Parts 1 and 2. Evidence of greater psychopathology in the mothers of burned children was supported by findings of both interview and self-report data, which indicated more symptoms of worry, depression, tension, anxiety, lack of energy, lower self confidence with other people and guilt, compared with mothers of Fracture Clinic and Normal Controls. Marital and social functioning and adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…12 An increased rate of divorce after the event has also been documented. 4, 22 Meyer et al found that mothers of burn-injured children reported higher levels of stress than the normative group. The mothers acknowledged that many of their own issues such as depression, role change, feelings of incompetence, marital strain, and social isolation had contributed to their increased stress levels after their child's injury.…”
mentioning
confidence: 98%
“…12 An increased rate of divorce after the event has also been documented. 4, 22 Meyer et al found that mothers of burn-injured children reported higher levels of stress than the normative group. The mothers acknowledged that many of their own issues such as depression, role change, feelings of incompetence, marital strain, and social isolation had contributed to their increased stress levels after their child's injury.…”
mentioning
confidence: 98%
“…Power was graded based on the smallest sample group (0 = n < 1 , 1 = n 1 -n 2 , 2 = n 3 -n 4 , 3 = n 5 -n 6 , 4 = n 7 -n 8 , 5 = n > 8 ), and all other items graded zero (no) or one (yes); possible maximum score of 31. Hooper et al's classifications [42] were adapted to provide overall quality rankings of poor (≤14), fair (15)(16)(17)(18)(19), good (20)(21)(22)(23)(24)(25), or excellent (26)(27)(28)(29)(30)(31). Assessment and data extraction were conducted by the lead author for all studies, and independently by two coauthors for 50% of studies.…”
Section: Assessment Of Cultural Components Study Quality and Risk Ofmentioning
confidence: 99%
“…The impact of burn related pain and distress is further exacerbated for paediatric burn patients who have a limited understanding of their injury and treatment [20], restricted agency in their care [21], and reduced ability to cope with the unpredictability of a hospital setting [22]. The struggles faced by paediatric burn patients is also greatly felt by their caregivers [20] who often experience overwhelming feelings of guilt, worry, panic, and anxiety whilst struggling with drastic shifts in their parenting role and ability to assist their child [23]. A review of empirical data highlights that 10-20% of paediatric burn patients and 4-42% of their caregivers reportedly experience symptoms of PTSD following the burn injury [24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated that PTSD was prevalent in parents of children who suffered burn injuries [16,19,[21][22][23][24]. Rivlin et al found that mothers of burned children reported a number of mental health problems such as greater degrees of worry, panic attacks with autonomic symptoms, depressed mood, and hopelessness about the future compared to mothers of children with fractures and controls [25].…”
mentioning
confidence: 99%
“…Other than one study which reported posttraumatic stress disorder among 48 mothers 11 years after a child suffered from a burn injury [29], the longest follow up was 6 months for 40 mothers of burn injured children [15]. Existing studies also primarily focussed on maternal mental health rather than the mental health of both parents [15,18,21,24,25]. One study that did include a significant number of fathers (n=154) in addition to mothers (n=182) was primarily focussed on acute stress reactions among couples [27].…”
mentioning
confidence: 99%